Design and assembly of new non-viral RNAi delivery agents by microwave-assisted quaternization (MAQ) of tertiary amines - Ghosh, Animesh (2010)
RNA interference (RNAi), a gene-silencing phenomenon whereby double-stranded RNA (dsRNA) triggers the sequence-specific degradation of homologous mRNA. RNAi has been quickly and widely applied to discover gene functions and holds great potential to provide a new class of therapeutic agents. However, new chemistry and delivery approaches are greatly needed to silence disease-causing genes without toxic effects. We reasoned that conjugation of the cholesterol moiety to cationic lipids would enhance RNAi efficiencies and lower the toxic effects of lipid-mediated RNAi delivery. Here, we report the first design and synthesis of new cholesterol-conjugated cationic lipids for RNAi delivery using microwave-assisted quaternization (MAQ) of tertiary amines. This strategy can be employed to develop new classes of non-viral gene delivery agents under safe and fast reaction conditions.